Part VI – June 1968 - Papers - The Determination of Water Vapor in Tough Pitch Copper Wire Bar by an Aluminum Reduction Technique - Charles L. Thomas; John C. Gifford (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
A unique and reproducible method is presented for the determination of water vapor in tough pitch wire bar copper. The procedure involves reduction of the water vapor with molten aluminum to form hydrogen, which is subsequently measured by mass spectroscopy. Average water vapor pressures within the porosities of the wire bar samples are calculated. Correlation is to exist between the specific gravities of the samples and their measured water vapor contents. The method should find application as a very sensitive means of detecting hydrogen embrittlement in copper. The nature and quantity of gases evolved and retained during the horizontal casting of tough pitch wire bar copper have long been of interest to the metallurgist. Considerable work has been done at this laboratory on the determination of these gases. The work has involved not only qualitative but also quantitative analysis, so as to provide a basis for a total accounting of the porosity which is associated with the cast product. From a knowledge of the gas-forming elements within the copper, and the practice of melting and protecting it with a reducing flame followed by contact with a charcoal cover in the casting ladle, the gases which one might expect to find in the pores of the cast product are sulfur dioxide, carbon monoxide, carbon dioxide, hydrogen, and water vapor. Hydrogen sulfide, nitrogen, and hydrocarbons would be other possibilities; however vacuum fusion-mass spectroscopy techniques employed at this laboratory have shown that no hydrogen sulfide and only traces of nitrogen and methane are present. It is highly improbable according to phillipsl that any sulfur dioxide could be evolved in wire bar copper with 10 ppm or less sulfur under normal freezing conditions. Mackay and smith2 have noted that porosity due to sulfur dioxide only becomes noticeable at concentrations above 20 ppm S. Investigation of carbon monoxide and carbon dioxide by a variation in the method of Bever and Floe showed that these two gases could only account, at 760 mm and 1064°C (Cu-Cua eutectic temperature), for a maximum of about 25 pct of the total porosity in a wire bar having a specific gravity of 8.40 g per cu cm. phillips' has noted that no normal furnace atmosphere is ever sufficiently rich in hydrogen to cause porosity in copper from hydrogen alone. In addition, using a hot vacuum extraction technique for hydrogen,4 values have never been observed in excess of 10 ppb in tough pitch wire bar. On the basis of the preceding considerations of gases in tough pitch wire bar, only water vapor is left to account for the major portion of the porosity. Direct determinations of water vapor are virtually impossible at low concentrations by any presently known technique, due to adsorption and desorption within the walls of the apparatus used.5 The present investigation deals with a method for the determination of water vapor by an indirect procedure, using molten aluminum as a reducing agent to form hydrogen according to the reaction: 2A1 + 3H2O — A12O3 + 3H2 The evolved hydrogen can then be measured quantitatively by mass spectroscopy. EXPERIMENTAL A 10-g piece of 99.9+ pct A1 was charged into a porous alumina crucible (Laboratory Equipment Co., No. 528-30). Fig. 1 shows the crucible in place at the bottom of an 8-in.-long quartz thimble. A funnel tube with two l1/8-in.-OD sidearms extending at a 90-deg angle from each other was attached to the top of the thimble. One of the sidearms was joined to the inlet system of the mass spectrometer (Consolidated Electrodynamics Corp. Model 21-620A) via a mercury diffusion pump situated between two dry-ice traps. The copper samples were placed in the other sidearm, followed by a glass-enclosed magnetic stirring bar for pushing the samples into the crucible. All ground joints were sealed with vacuum-grade wax. The entire system was evacuated and the aluminum was heated with a T-2.5 Lepel High Frequency Induction Furnace for 21/2 hr at a temperature visually estimated to be 900°C. The temperature was then lowered and the hydrogen was monitored on the mass spectrometer until it was given off at a constant rate of about 4 to 5 1 per hr. This rate corresponded to a slope of 2 to 3 divisions per min on the X3 attenuation of a 10-mv recorder at a hydrogen sensitivity of approximately 100 divisions per 1. A micromanometer (Consolidated Electrodynamics Corp. Model 23-105)